Analisis Pengaruh Pemahaman Modul Penerimaan Negara (Mpn) Terhadap Tingkat Kepatuhan Wajib Pajak Pada Kpp Pratama Kedaton (Study Kasus pada KPP Pratama Kedaton) - . Khomsiyah; Rico Yanuar; Rosmiaty Tarmizi (Jurnal Akuntansi dan Keuangan, 2012)
The purpose of this study was to analyze the influence of the understanding module of State Revenue (MPN) on the level of tax compliance on STO Kedaton. Based on the analysis of the answers to the questionnaire, the level of understanding of the corporate taxpayers Module Revenues (MPN) of 73.3% and is in the category understand. While the level of tax compliance on STO Kedaton at 71.1% and is in the category submissive. Despite this level of understanding of the taxpayer Module Revenues (MPN) and the level of tax compliance on STO Kedaton not yet reached optimal levels. This is because the government lacks in socializing Module Revenues (MPN). Besides the lack of government in delivering superior service to taxpayers and given sanctions still looks less than the maximum, giving rise to a lack of tax compliance in paying taxes. Based on the analysis results, the authors suggest to STO Kedaton to improve socialization MPN MPN for taxpayers because it can provide a substantial contribution to improving taxpayer compliance in paying taxes. Furthermore, it provides strict penalties for taxpayers who "naughty" and provide better service tax for taxpayers so that taxpayers can feel easy and comfortable in paying taxes. For further research to develop this research further.